Laser crystal material and preparation method and application thereof
By developing a new laser crystal material, Ca3Yb2AlGaO9, and growing using melt lifting method, it solves the problem that existing laser crystals are difficult to take into account high power and short pulse width, and realizes high-efficiency femtosecond laser output and wide-band infrared emission, suitable for all solid state Application of femtosecond laser.
Patent Information
- Application Number
- CN202411154991.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-08-21
AI Technical Summary
Existing laser crystals are difficult to take into account high power and short pulse width, and cannot effectively achieve ultra-wideband luminescence and ultra-short pulse performance, which limits the development and application of femtosecond laser technology.
A new laser crystal material, Ca3Yb2AlGaO9, was developed, grown by melt lifting method, with ultra-wideband absorption and emission performance, with a peak wavelength of 996nm, and is suitable for femtosecond laser output of 950-1070nm infrared band under 939nm pump.
It realizes high power and high efficiency femtosecond laser output, enhances fluorescence emission in the ~1 micron infrared band, has good physical and chemical properties and thermal conductivity, and is suitable for the application of all-solid-state femtosecond lasers.
Smart Images

Figure CN119243334A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a laser crystal material and a preparation method and application thereof, and belongs to the field of inorganic functional crystal materials. Background Art
[0002] Femtosecond laser is an ultra-strong and ultra-fast laser technology that developed rapidly in the early 1980s. Unlike other long-pulse lasers and continuous lasers, it has characteristics such as ultra-short pulses, ultra-high electric fields and ultra-wide spectrums, and is an extreme physical condition that can be achieved in a laboratory. Ultra-short pulse durations only require a small amount of laser energy (μJ) to produce extremely high instantaneous power at the focal point, up to one trillion watts, and its focusing intensity is higher than the energy density of all the light radiated from the sun to the earth after it is focused into a needle-like size. Femtosecond laser pulses can generate plasma, and when they interact with matter, they can produce a variety of phenomena based on the nonlinear interaction between light and matter. Therefore, femtosecond laser technology has been widely used in various fields such as information, energy, environment, medicine, national defense and basic scientific research.
[0003] Femtosecond lasers in the infrared band of 1 micron have attracted great attention due to their unique advantages. They have important applications in all-solid-state lasers, biomedicine, industrial processing, etc. At present, the realization of 1 micron lasers is mostly achieved by pumping Yb-doped lasers with semiconductor laser diodes (LDs). 3+ The gain medium can directly obtain 1 micron laser, with simple device, compact structure, high laser output power and optical-to-optical conversion efficiency. 3+ ) gain medium mode-locked lasers have the widest application. Commonly used Yb-doped crystals include Yb:YAG, Yb:CaF2, Yb:CaGdAlO4, Yb:CaYAlO4, etc., which have obvious advantages in wide emission spectrum and few quantum defects. However, it is difficult for existing laser crystals to take into account both high power and short pulse width. Therefore, discovering new laser crystals with ultra-wideband luminescence and ultra-short pulse properties is still a hot research direction in the field of all-solid-state lasers. Summary of the invention
[0004] The present application provides a laser crystal material Ca3Yb2AlGaO9, which is a brand-new femtosecond laser crystal material. The crystal is grown by melt pulling method. The laser crystal material is an excellent laser matrix crystal, which uses 939nm pumping to generate ultra-wideband fluorescence emission in the 950-1070nm band, with a peak wavelength of 996nm. The laser crystal material can be used to generate wide-band infrared femtosecond laser.
[0005] According to a first aspect of the present application, a laser crystal material is provided.
[0006] A laser crystal material, wherein the chemical formula of the laser crystal material is Ca3Yb2AlGaO9.
[0007] Optionally, the laser crystal material belongs to the monoclinic system, P21 / c space group.
[0008] Optionally, the unit cell parameters of the laser crystal material are α=γ=90°, β=107~109°, Density: 6.14~6.16g·cm -3 .
[0009] Specifically, the unit cell parameters of the laser crystal material are β=108°, Density: 6.15 g cm -3 .
[0010] Optionally, the laser crystal material is in block shape;
[0011] The laser crystal material has at least one dimension with a size of 35 to 66 mm.
[0012] Optionally, the laser crystal material has a diameter of 25-35 mm and a length of 45-66 mm.
[0013] Optionally, the absorption spectrum of the laser crystal material contains a broadband absorption peak with a peak wavelength of 980 nm in the 900-1025 nm band.
[0014] Optionally, in the fluorescence spectrum of the laser crystal material under 939 nm pumping, there is a broadband emission peak with a peak wavelength of 996 nm in the 950-1070 nm band.
[0015] The laser crystal material has good physical and chemical properties, does not absorb moisture in the air, and the crystal is insoluble in acid and alkali. It has a high melting point, high mechanical strength, high laser damage threshold, and high thermal conductivity.
[0016] According to a second aspect of the present application, a method for preparing the laser crystal material described above is provided.
[0017] The method for preparing the laser crystal material described above adopts a melt-pulling method and comprises the following steps:
[0018] S1. Obtain Ca3Yb2AlGaO9 polycrystalline raw material rod;
[0019] S2. Weigh the raw materials of CaCO3, Yb2O3, Ga2O3 and Al2O3 according to the stoichiometric ratio, grind and mix them, press them into blocks, sinter them to generate polycrystalline materials, heat and melt them, use Ca3Yb2AlGaO9 polycrystalline raw material rods as seed crystals for introduction, and then grow crystals after crystals are formed on the seed crystals to obtain the laser crystal material.
[0020] Optionally, the Ca3Yb2AlGaO9 polycrystalline raw material rod is produced by hot isostatic pressing.
[0021] Optionally, the size of the Ca3Yb2AlGaO9 polycrystalline raw material rod is Φ6mm×50mm.
[0022] Optionally, the molar ratio of CaCO3, Yb2O3, Ga2O3 and Al2O3 is CaCO3﹕Yb2O3﹕Ga2O3﹕Al2O3=6:2:1:1.
[0023] Optionally, the crystal growth conditions are:
[0024] The pulling rate is 0.5-1.8 mm / h, the rotation speed of the seed crystal rod is 5-12 rpm, the growth rate is 0.7-1.3 mm / h, and after the growth is completed, the crystal is lifted from the liquid surface and cooled to room temperature at a rate of 15-65°C / h.
[0025] Optionally, the purity of CaCO3, Yb2O3, Ga2O3 and Al2O3 is 99.999%.
[0026] Optionally, raw materials containing CaCO3, Yb2O3, Ga2O3, and Al2O3 are weighed according to a stoichiometric ratio, put into a homemade mixer for wet mixing, pressed into blocks at 25 MPa, and placed in a sintering furnace for high-temperature sintering at 1350°C for 48 hours, and then heated and melted in a single crystal growth furnace, using Ca3Yb2AlGaO9 polycrystalline raw material rods as seed crystals for introduction, and crystals are grown after crystals are formed on the seed crystals.
[0027] As a specific implementation, the method for preparing the laser crystal material comprises at least the following steps:
[0028] CaCO3, Yb2O3, Ga2O3 and Al2O3 are used as raw materials, wherein the molar ratio of CaCO3, Yb2O3, Ga2O3 and Al2O3 is CaCO3:Yb2O3:Ga2O3:Al2O3=6:2:1:1, and each chemical substance is weighed and finely ground according to the molar ratio. The raw materials CaCO3, Yb2O3, Ga2O3 and Al2O3 are mixed and pressed into sheets, and then placed in an iridium crucible of a crystal growth furnace, evacuated and heated to 1860°C for melting, and then a Φ6mm×50mm Ca3Yb2AlGaO9 polycrystalline raw material rod made by hot isostatic pressing equipment is selected as a seed crystal for introduction for crystal growth. The growth conditions are: a pulling rate of 0.5-1.8mm / h, and a rotation rate of the seed crystal rod of 5-12rpm. After the growth is completed, the crystal is lifted from the liquid surface and cooled to room temperature at a rate of 15-65°C / h to obtain the block crystal with a diameter of 25-35mm and a length of 45-66mm.
[0029] According to a third aspect of the present application, there is provided an application of the above-mentioned laser crystal material in infrared femtosecond laser.
[0030] The laser crystal material is used for realizing the output of femtosecond laser with a wavelength in the infrared band of 950-1070nm under 939nm pumping.
[0031] According to a fourth aspect of the present application, an all-solid-state femtosecond laser is provided.
[0032] An all-solid-state femtosecond laser comprises the laser crystal material described above.
[0033] Optionally, the all-solid-state femtosecond laser further includes an LD end-face pump module, a beam coupling system, an input mirror, a folding mirror, a chirped mirror, and a SESAM output mirror;
[0034] The beam coupling system is located behind the LD end-face pump module;
[0035] The input mirror is located after the beam coupling system;
[0036] The folding mirror is located behind the input mirror;
[0037] The chirped mirror is located behind the folding mirror;
[0038] The SESAM output mirror is located after the chirped mirror;
[0039] The laser crystal material is located between the input mirror and the folding mirror.
[0040] Optionally, the pump source of the LD end-face pump module is a 939nm InGaAs LD;
[0041] The pumping mode is end-face pumping, and the pumping source is a fiber-coupled semiconductor laser;
[0042] The laser resonant cavity is a plano-concave cavity with a total cavity length of 58 mm;
[0043] The input mirror is a plane mirror, and the mirror surfaces on both sides are coated with a 939nm anti-reflection film and a 1035-1060nm high-reflection film respectively;
[0044] The output mirror is a concave mirror with a curvature radius of 75 mm and a transmittance of 3%.
[0045] The beneficial effects of this application include:
[0046] 1) The laser crystal material Ca3Yb2AlGaO9 provided in the present application has ultra-wideband absorption and emission properties. The laser crystal material can achieve tunable femtosecond laser output with a wavelength in the infrared band of 950 to 1070 nm under 939 nm pumping.
[0047] 2) The laser crystal material Ca3Yb2AlGaO9 provided in this application is different from the ordinary Yb 3+ Doped aluminates such as CaGdAlO4, CaYAlO4 and Y3Al5O 12 Compared with other crystals, it has the following advantages: Ca3Yb2AlGaO9 has the structural characteristics of disordered atomic distribution, and its absorption cross section and half-peak width are large, which is conducive to the crystal's absorption of pump light, thereby enhancing the crystal's fluorescence emission in the infrared band of ~1 micron; it has a large emission cross section and half-peak width, as well as strong fluorescence emission, which is very beneficial to laser output, helps to increase the emission power and efficiency of femtosecond lasers, and helps to compress the pulse width. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 It is the Ca3Yb2AlGaO9 crystal grown by the pulling method in Example 1.
[0049] Figure 2 This is the X-ray powder diffraction pattern of Ca3Yb2AlGaO9 crystal, compared with the standard card (No. 14-0475).
[0050] Figure 3 This is the room temperature absorption spectrum of Ca3Yb2AlGaO9 crystal.
[0051] Figure 4 This is the fluorescence spectrum of Ca3Yb2AlGaO9 crystal in the infrared band under 939nm pumping.
[0052] Figure 5This is a schematic diagram of the device for laser experiments using Ca3Yb2AlGaO9 crystals, where M1, M2, and M3 are input mirror, folding mirror, and chirped mirror, respectively; laser diode and SESAM are laser semiconductor pump sources and semiconductor saturable absorber mirrors, respectively. DETAILED DESCRIPTION
[0053] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0054] Unless otherwise specified, the raw materials and reagents used in this application were purchased from commercial sources and used directly without treatment. The instruments and equipment used adopted the schemes and parameters recommended by the manufacturers.
[0055] In the embodiment, the instrument used for the crystal pulling method growth is a DJL-600 crystal growth furnace, the crucible used is an iridium crucible of Ф80mm×80mm, and the raw materials used are CaCO3, Yb2O3, Ga2O3 and Al2O3 with a purity of 99.999%.
[0056] In the examples, powder X-ray analysis of the samples was carried out on a Miniflex 600 powder diffractometer.
[0057] In the examples, the absorption spectra of the samples were measured on a Lambda950 absorption spectrometer produced by Pekin-Elmer; and the fluorescence spectra under 939 nm pumping were measured on a FLS980 fluorescence spectrometer produced by Edinburgh, UK.
[0058] Example 1 Preparation of large-size single crystal samples of Ca3Yb2AlGaO9
[0059] CaCO3, Yb2O3, Ga2O3 and Al2O3 are prepared according to the following chemical reaction formula:
[0060] 6CaCO3+2Yb2O3+Ga2O3+Al2O3→2Ca3Yb2AlGaO 9+ 6CO2↑
[0061] According to the above molar ratio of CaCO3﹕Yb2O3﹕Ga2O3﹕Al2O3=6:2:1:1, weigh CaCO3, Yb2O3, Ga2O3 and Al2O3, the total weight of the raw materials is 2400g, mix them evenly, use a hydraulic press to press them into cylindrical blocks at 25Mpa, place them in a sintering furnace for high temperature sintering at 1350℃ for 48h, put them into a Ф80mm×80mm iridium crucible, put them in a DJL-600 crystal growth furnace, evacuate, and slowly heat up at a rate of 250℃ / h The raw material is melted and kept at a constant temperature for 4 hours to completely melt the raw material. Then, a Φ6mm×50mm Ca3Yb2AlGaO9 polycrystalline raw material rod prepared by hot isostatic pressing equipment is used as the seed crystal for introduction. The preparation method is: place the Ca3Yb2AlGaO9 polycrystalline raw material powder prepared according to the chemical proportion into a closed cylindrical rubber container, apply an equal pressure of 200Mpa in all directions to the product, and at the same time apply a high temperature of 1000℃. Under the action of high temperature and high pressure, the product is sintered and densified to form a cylindrical raw material rod.
[0062] After the crystals are formed on the seed crystals, the crystals are grown. During the growth process, the growth rate is set to 1 mm / h, the pulling speed is set to 1 mm / h, and the rotation speed of the seed crystal rod is set to 8 rpm. After the growth is completed, the crystals are lifted from the liquid surface and cooled to room temperature at a rate of 40°C / h to obtain colorless and transparent crystals with a size of Φ27 mm×56 mm. The crystal photos are shown in FIG. Figure 1 shown.
[0063] Example 2 Crystal structure characterization of samples
[0064] A small piece was cut from the grown bulk crystal, finely ground into powder, and the structure of the crystal sample was determined using the X-ray diffraction method.
[0065] The measured diffraction pattern is compared with the XRD diffraction pattern of Y4Al2O9 standard card. Figure 2 As shown in the figure, it can be seen that the actual measured XRD spectrum is roughly consistent with the diffraction peak position of the substance in the standard card, indicating that the structure of the obtained sample is similar to it, and that the obtained crystal is a high-purity crystal Ca3Yb2AlGaO9 without impurities.
[0066] The crystal structure is analyzed and belongs to the monoclinic system, P21 / c space group, unit cell parameters α=γ=90°, β=108°,
[0067] The density is obtained by testing using the following method. The specific steps are:
[0068] Ⅰ. A square crystal of 5 mm × 5 mm × 5 mm was cut from Example 1 and its mass was measured on a balance to obtain m;
[0069] Ⅱ. Put an appropriate amount of water into a graduated cylinder, record its volume scale V1, then put the square crystal into the cylinder and read the volume scale V2;
[0070] Ⅲ. Repeat the above steps three times and record the experimental data each time;
[0071] IV. Calculate the density of the crystal according to the formula ρ = m(V2-V1), take the average of three experiments, and obtain a crystal density of 6.15 g cm -3 .
[0072] Example 3 Spectral performance measurement of samples
[0073] The grown bulk crystals were cut, processed and polished into pieces with dimensions of 10.0 × 10.0 × 1.0 mm. 3 X-cut crystal, two parallel surfaces through which light passes, 10.0×10.0mm 2 Polishing, and conducting spectral performance testing in E / / X direction.
[0074] The results show that Figure 3 As shown, the absorption spectrum of the sample shows that Yb 3+ The characteristic absorption peak of Yb has a wide absorption peak between 900-1025nm, with a peak wavelength of 980nm, corresponding to 3+ : 2 F 7 / 2 arrive 2 F 5 / 2 This absorption band matches the commercial InGaAs semiconductor pump source, making the crystal very suitable for laser experiments using commercial InGaAs diode pumping.
[0075] like Figure 4 As shown in the figure, the room temperature fluorescence spectrum of the sample under 939 nm pumping has a wide fluorescence emission band between 950 and 1070 nm, with a peak wavelength of 996 nm, corresponding to Yb 3+ : 2 F 5 / 2 → 2 F 7 / 2 The full width at half maximum (FWHM) is 75.8 nm, and the emission cross section calculated using the FL equation is 8.55×10 -21 cm 2 @996nm, the emission cross section and emission bandwidth are large, which is conducive to the realization of femtosecond laser output.
[0076] The above research and experimental results show that Ca3Yb2AlGaO9 crystal is a laser crystal material with great application prospects and can achieve femtosecond laser output in the 950-1070nm infrared band.
[0077] Application of Example 4 in Laser Device
[0078] X-cut crystal rods with a size of 3mm×3mm×8mm were processed from the grown Ca3Yb2AlGaO9 crystal, and the 3mm×3mm surfaces at both ends were polished for laser performance testing. The crystal was placed on a cooling device consisting of a temperature control table and a copper block. During the experiment, the crystal was maintained at a temperature of 7-8℃ with a control accuracy of 0.1℃. During the experiment, a layer of indium paper was placed between the copper table and the crystal for better heat dissipation. A 939nm InGaAs LD pump source was used for end pump operation. The pump light was focused at the center of the crystal after passing through a double-glued achromatic lens and a plane mirror 1. The laser resonator cavity consists of a plano-concave mirror with a total cavity length of 58mm. The input mirror is a plane mirror, and the mirror surfaces on both sides are coated with a 939nm anti-reflection film and a 1035-1060nm high-reflection film. The transmittance at 939nm is greater than 96%, and the reflectance at 1035-1060nm is greater than 99.7%. The output mirror is a concave mirror with a radius of curvature of 75mm and a transmittance of 3%. The schematic diagram of the experimental setup is as follows: Figure 5 As shown in the figure, the beam coupling system is located after the LD end-pumping module, and the laser diode is the laser semiconductor pump source of the LD end-pumping module; the input mirror M1 is located after the beam coupling system; the folding mirror M2 is located after the input mirror M1; the chirped mirror M3 is located after the folding mirror M2; the SESAM as a semiconductor saturable absorber is located after the chirped mirror M3; and the laser crystal is located between the input mirror M1 and the folding mirror M2. In the tunable laser experiment, the etalon is inserted as a wavelength selection element. The saturable absorber is located between the etalon and the output mirror. The results show that due to the disordered structure and broadened emission band of the Ca3Yb2AlGaO9 crystal, the laser exhibits a multi-wavelength output of 1035-1045nm, with a central wavelength of about 1035nm. Further adjusting the pump power and laser parameters, a hundred-femtosecond laser output was achieved. Moreover, the repetition frequency and pulse width show an opposite change law, that is, a larger repetition frequency corresponds to a narrower pulse width, showing a typical passive Q-switching change law.
[0079] Therefore, the new crystal Ca3Yb2AlGaO9 provided by the present invention is a very excellent femtosecond laser gain material.
[0080] The several embodiments of the present application are not intended to limit the present application in any form. Although the present application is disclosed as above with preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above-disclosed technical contents to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A laser crystal material, characterized in that: The chemical formula of the laser crystal material is Ca3Yb2AlGaO9.
2. The laser crystal material according to claim 1, characterized in that: The laser crystal material belongs to the monoclinic system and the P21 / c space group.
3. The laser crystal material according to claim 1, characterized in that: The unit cell parameters of the laser crystal material are: α=γ=90°, β=107~109°, Density: 6.14~6.16g·cm -3 ; Preferably, the unit cell parameters of the laser crystal material are β=108°, Density: 6.15 g cm -3 .
4. The laser crystal material according to claim 1, characterized in that: The laser crystal material is in block shape; The laser crystal material has at least one dimension with a size of 35 to 66 mm; Preferably, the diameter of the laser crystal material is 25-35 mm and the length is 45-66 mm.
5. The laser crystal material according to claim 1, characterized in that: The absorption spectrum of the laser crystal material contains a broadband absorption peak with a peak wavelength of 980 nm in the 900-1025 nm band; Preferably, the fluorescence spectrum of the laser crystal material under 939 nm pumping contains a broadband emission peak with a peak wavelength of 996 nm in the 950-1070 nm band.
6. The method for preparing a laser crystal material according to any one of claims 1 to 5, characterized in that: The preparation method adopts a melt pulling method, comprising the following steps: S1. Obtain Ca3Yb2AlGaO9 polycrystalline raw material rod; S2. Weigh the raw materials of CaCO3, Yb2O3, Ga2O3 and Al2O3 according to the stoichiometric ratio, grind and mix them, press them into blocks, sinter them to generate polycrystalline materials, heat and melt them, use Ca3Yb2AlGaO9 polycrystalline raw material rods as seed crystals for introduction, and then grow crystals after crystals are formed on the seed crystals to obtain the laser crystal material.
7. The preparation method according to claim 6, characterized in that: The Ca3Yb2AlGaO9 polycrystalline raw material rod was prepared by hot isostatic pressing; Preferably, the size of the Ca3Yb2AlGaO9 polycrystalline raw material rod is Φ6mm×50mm; Preferably, the molar ratio of CaCO3, Yb2O3, Ga2O3 and Al2O3 is CaCO3:Yb2O3:Ga2O3:Al2O3=6:2:1:
1.
8. The preparation method according to claim 6, characterized in that: The conditions for the crystal growth are: The pulling rate is 0.5-1.8 mm / h, the rotation speed of the seed crystal rod is 5-12 rpm, the growth rate is 0.7-1.3 mm / h, and after the growth is completed, the crystal is lifted from the liquid surface and cooled to room temperature at a rate of 15-65°C / h.
9. Application of the laser crystal material according to any one of claims 1 to 5 in infrared femtosecond laser; Preferably, the laser crystal material is used to realize the output of femtosecond laser with a wavelength in the infrared band of 950-1070nm under 939nm pumping.
10. An all-solid-state femtosecond laser, characterized in that: The all-solid-state femtosecond laser comprises the laser crystal material according to any one of claims 1 to 5; Preferably, the all-solid-state femtosecond laser further comprises an LD end-face pump module, a beam coupling system, an input mirror, a folding mirror, a chirped mirror, and a SESAM output mirror; The beam coupling system is located behind the LD end-face pump module; The input mirror is located after the beam coupling system; The folding mirror is located behind the input mirror; The chirped mirror is located behind the folding mirror; The SESAM output mirror is located after the chirped mirror; The laser crystal material is located between the input mirror and the folding mirror.
Citation Information
Patent Citations
Mn<2+> doped yellow long-lasting phosphor material and preparation method thereof
CN107418571A
Inorganic crystal material as well as preparation method and application thereof
CN115852486A
Monocline type gadolinium aluminate based fluorescent powder and method for making same
CN1670125A
